2003
DOI: 10.1002/mrm.10611
|View full text |Cite
|
Sign up to set email alerts
|

k‐t BLAST and k‐t SENSE: Dynamic MRI with high frame rate exploiting spatiotemporal correlations

Abstract: Dynamic images of natural objects exhibit significant correlations in k-space and time. Thus, it is feasible to acquire only a reduced amount of data and recover the missing portion afterwards. This leads to an improved temporal resolution, or an improved spatial resolution for a given amount of acquisition. Based on this approach, two methods were developed to significantly improve the performance of dynamic imaging, named k-t BLAST (Broad-use Linear Acquisition Speed-up Technique) and k-t SENSE (SENSitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
835
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 767 publications
(840 citation statements)
references
References 31 publications
2
835
0
3
Order By: Relevance
“…As far as the achievable image quality is concerned, the present results may be even further improved by exploiting frame-to-frame temporal redundancies, which are inherently contained in a dynamic image series of the beating heart. Such ideas have previously been shown to improve the reconstruction quality of linear algorithms (13)(14)(15)(16) and will be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the achievable image quality is concerned, the present results may be even further improved by exploiting frame-to-frame temporal redundancies, which are inherently contained in a dynamic image series of the beating heart. Such ideas have previously been shown to improve the reconstruction quality of linear algorithms (13)(14)(15)(16) and will be the subject of future work.…”
Section: Discussionmentioning
confidence: 99%
“…For multidirectional velocity-encoding PC-MRI, ACS lines are typically acquired separately for each velocity direction and each cardiac timeframe. More advanced imaging acceleration techniques such as TGRAPPA (time-interleaved sampling scheme in combination with GRAPPA), TSENSE (adaptive sensitivity encoding incorporating temporal filtering), and several k-t-space related reconstructions, i.e., k-t GRAPPA, PEAK-GRAPPA (parallel MRI with extended and averaged GRAPPA kernels), k-t BLAST (broad-use linear acquisition speed-up technique), and kt SENSE (sensitivity encoding), have recently been reported that exploit the possibility to efficiently undersample both the spatial and temporal dimensions (12)(13)(14)(15)(16). As a result, higher reduction factors can be achieved compared to standard techniques such as GRAPPA or SENSE (5,10).…”
Section: Dynamic Phase Contrast (Pc) Mrimentioning
confidence: 99%
“…1). To evaluate the effect of the number of ACS lines, reduction factors, and retaining central k-lines, images were reconstructed with ACS ¼ [16,32], R ¼ [2,3,4], and [0, 4,8] retained central k-lines (in total, 18 combinations), respectively. As for the true reduction factor of each reconstructed algorithm, the number of used k-line was divided by the number of total k-line of the fully sampled data set.…”
Section: Blood Flow: Mri Data Acquisition and Image Reconstructionmentioning
confidence: 99%
“…In TSENSE and TGRAPPA a time-interleaved acquisition scheme allows for a direct merging of adjacent timeframes in order to build a fully encoded reference dataset which is then used to derive sensitivity information or autocalibration signal. In contrast, k-t-SENSE, k-t-BLAST, and k-t-GRAPPA directly incorporate the temporal information into the reconstruction process, thus allowing for higher acceleration factors than available coil elements since these techniques can be treated as a combination of the conventional parallel imaging methods (GRAPPA, SENSE) and sliding window techniques (4,7).…”
mentioning
confidence: 99%